Lymphedema: A General Outline of Its Anatomical Base - Amore, M.; Tapia, L.; Mercado, D.; Pattarone, G.; Ciucci, J. (Journal of Reconstructive Microsurgery, 2016)
The anatomic research of the lymphatic system has been a very controversial subject throughout due to the complexity of the methods for its visualization. More than 30 years ago, together with Prof. Caplan, we began the vascular anatomy research, focusing on the lymphatic anatomy, developing and adapting different techniques of injection. On the third Normal Anatomy Chair of Buenos Aires University, we summarized the lymphatic drainage of the breast and the limbs to interpret the anatomic bases of lymphedema.
Keywords: lymphedema; lymphatics anatomy; mammary gland